Mass oestrus synchronization programme in dairy animals: A field experience - Soni, Y K; Kumar, S; Saha, S; Chand, N; Pande, M; Prasad, N (Indian Farming, 2019)
Oestrus synchronization is a reproductive management technique through which most of the female animals in a herd can be brought to oestrus at a predetermined time. It allows dairy producers to plan breeding of their animals during the most favourable season of the year, enhance pregnancy rates, reduce time and labour spent on heat detection, produce of calf for the future herd replacement, and hence contribute to the dairy economy.